Chemical composition of yak colostrum and transient milk. Issue 5 (24th December 2014) - Cui, N.; Wen, P. C.; Liang, Q.; Liu, H. N.; Zhang, W. B.; Wang, P. J.; Guo, H. Y.; Ren, F. Z.
Summary: The objective of this study was to assess the changes in the chemical composition of yak colostrum and transient milk. Samples were collected from 12 yaks on days 1, 2, 3, 4, 5, 6 and 7 post‐partum (PP). The gross composition, nitrogen fraction distribution, amino acid (AA) profile and fatty acid (FA) profile were analysed. All the components decreased rapidly during the first 3 days except lactose which increased. The ratio of whey protein to casein protein decreased from 46:54 to 17:83 during the first 7 days PP. The content of all the AAs decreased, while the percentages of eight essential AAs in protein of samples increased during the study period. Monounsaturated FAs and polyunsaturated FAs decreased in the first 7 days PP, whereas saturated FAs increased. In conclusion, the changes in chemical composition were remarkable during the first 3 days. The slight variations, happened during the transient period, are not negligible, which also should be taken into account in the development of yak colostrum supplements.